Profiling of relaxin and its receptor proteins in boar reproductive tissues and spermatozoa - Feugang, Jean M (Reprod Biol Endocrinol, 2015)
BACKGROUND: Relaxin levels in seminal plasma have been associated with positive effects on sperm motility and quality, and thus having potential roles in male fertility. However, the origin of seminal relaxin, within the male reproductive tract, and the moment of its release in the vicinity of spermatozoa remain unclear. Here, we assessed the longitudinal distribution of relaxin and its receptors RXFP1 and RXFP2 in the reproductive tract, sex accessory glands, and spermatozoa of adult boars. METHODS: Spermatozoa were harvested from three fertile boars and reproductive tract (testes and epididymis) and sex accessory gland (prostate and seminal vesicles) tissues were collected post-mortem from each boar. Epididymis ducts were sectioned into caput, corpus, and cauda regions, and spermatozoa were mechanically collected. All samples were subjected to immunofluorescence and/or western immunoblotting for relaxin, RXFP1, and RXFP2 detection. Immunolabeled-spermatozoa were submitted to flow cytometry analyses and data were statistically analyzed with ANOVA. RESULTS: Both receptors were detected in all tissues, with a predominance of mature and immature isoforms of RXFP1 and RXFP2, respectively. Relaxin signals were found in the testes, with Leydig cells displaying the highest intensity compared to other testicular cells. The testicular immunofluorescence intensity of relaxin was greater than that of other tissues. Epithelial basal cells exhibited the highest relaxin immunofluorescence intensity within the epididymis and the vas deferens. The luminal immunoreactivity to relaxin was detected in the seminiferous tubule, epididymis, and vas deferens ducts. Epididymal and ejaculated spermatozoa were immunopositive to relaxin, RXFP1, and RXFP2, and epididymal corpus-derived spermatozoa had the highest immunoreactivities across epididymal sections. Both vas deferens-collected and ejaculated spermatozoa displayed comparable, but lowest immunofluorescence signals among groups. The entire sperm length was immunopositive to both relaxin and receptors, with relaxin signal being robust in the acrosome area and RXFP2, homogeneously distributed than RXFP1 on the head of ejaculated spermatozoa. CONCLUSIONS: Immunolocalization indicates that relaxin-receptor complexes may have important roles in boar reproduction and that spermatozoa are already exposed to relaxin upon their production. The findings suggest autocrine and/or paracrine actions of relaxin on spermatozoa, either before or after ejaculation, which have possible roles on the fertilizing potential of spermatozoa.